Mesoporous x[Cu(II)O] nanoclusters dispersed and immobilized on y [SiO 2] matrix: structure and effective controlled biocidal activity against Pseudomonas aeruginosa and Bacillus subtilis - Banik, D.; Chennakesavulu, S.; Singh, M.; Pandey, N.; Tilak, R.; Reddy, A.B.M.; Paik, P. (Springer, 2020)
Herein we report the synthesis of mesoporous nanostructures comprising copper (II) oxide { x[Cu (II) O] } immobilized on silica y[SiO 2] template for release of copper ions by precipitation via sol–gel technique. Three different specimens with increasing amount of Cu in the matrix with amount of Si being the same in all the samples, viz. ‘6Cu:5Si’, ‘4.5Cu:5Si’ and ‘3Cu:5Si’ where the numbers refer to the respective molar ratios of their respective domains, were prepared. Increase of crystallinity in the mesoporous material with increase in incorporation of copper domains consisting of CuO in SiO 2 matrix has been established. The average size of the CuO nanoparticle (NP) (domain) is 20–30 nm. The BET surface area has been found to be 276–390 m2g-1 and Langmuir surface area has been found to be 422–605.9 m2g-1 for the samples 5Si:3Cu–5Si:6Cu, respectively, having pore size of 4–6.5 nm. The cytotoxicity data show that the NPs are less toxic below concentration of 125μgml-1. A steady increase in percentage of bacterial-‘Escherichia coli’, ‘Pseudomonas aeruginosa’ and ‘Bacillus subtilis’ cell death (indicated by decrease in optical density) due to increase in concentrations of NPs after incubation for 14 h, showing sensitivity even at very low concentrations (5–20 μ g), has been observed. A comparative antibacterial activity test among the three prepared specimens has been reported, which shows better antibacterial activity with the lowest copper concentration. Better antibacterial sensitivity when compared with equivalent amount of commercial CuO is established. © 2020, Indian Academy of Sciences.
Keywords: x[Cu(II)O]·y[SiO2] nanoparticles; mesopore; antibacterial activity; Pseudomonas aeruginosa; Bacillus subtilis